Keterlibatan Pekerja Wanita yang telah Berkeluarga di Sektor Industri - Jusniati Jusniati; Suharty Roslan; Bakri Yusuf (LP3M Universitas Muhammadiyah Kendari, 2023)
This study analyzes the social and economic factors that motivate women to work in the public sector at PT. X in Kendari City. Social aspects such as considerations for their children's future, husband's occupation, and self-actualization, as well as economic aspects like husband's income, household expenditures, and the desire to save, influence women's decision to work. Their time allocation is divided between work and household tasks, with 8 hours for work and 16 hours used for household chores and rest. Nevertheless, they still financially contribute to the family and depend on family support in caring for their children. The presence of female workers at PT. X impacts their families, highlighting the intricate balance between work and family responsibilities. Support for female workers through flexible work arrangements, time management, and safe childcare facilities is crucial in alleviating their burden. The conclusion of this study underscores the interplay between social and economic factors in women's workforce participation, with systemic support aiding in maximizing their roles in both professional and family environments.